Analisis Kesiapan Penggunaan Digital Finance pada UMKM di Kota Palopo Perspektif I-TOE Model - Supri, Zikra; Dewintari, Putri; Nadia; Risdayanti (Politeknik Ganesha Medan, 2024)
Digital finance can help improve the effectiveness and efficiency of business processes and operations, especially Micro, Small and Medium Enterprises ( SMEs ). Productive SMEs are one of the main keys in driving the acceleration of national economic recovery. The Financial Services Authority (OJK) also explained the importance of Digital finance's contribution in supporting the achievement of Sustainable Development Goals (SDGs). The urgency of the research is related to the use of digital finance which is still not massive among SMEs in Palopo City, one of which is caused by the readiness of SMEs in using digital finance. This study aims to determine the readiness of SMEs in using digital finance. The research method uses a quantitative approach based on the Individual - Technology Organization Environment (I-TOE) model by involving SMEs in Palopo City as respondents. The population is SMEs who live in Palopo city, and the sampling technique uses simple random sampling. Data collection is done through surveys / questionnaires both manually and online. The data analysis technique in this study used multiple linear regression. The results showed that partially the technology and environmental variables had a positive effect on the readiness of SMEs to use digital finance. as well as for individual and organizational variables showed results that had no effect. Meanwhile, the results of the simultaneous test can explain that the Independent variables (Environment, Organization, Individual and Technology) affect the readiness to use digital finance variable.